Self-inflicted traumatic ulcer due to preoperative anxiety in children: Ulser traumatik self-inflicted yang disebabkan kecemasan preoperasi pada anak - Adi Ahmad Yusuf; Tenny Setiani Dewi (Makassar Dental Journal, 2022)
Introduction: Self-inflicted traumatic ulcers are oral lesions caused by the patient himself, that can be caused to intentional bad habits, accidents or habits thatoccur without realizing it. Self-inflicted lesions are present in about 75% of the head and neck area, and can be caused by biting tissue in the oral cavity or inserting foreign bodies and nails into the oral mucosa. Case: It is reported a case of traumatic self-inflicted ulcer in a 4-year-old child. This patient was diagnosed with intra-abdominal tumors and plan-ned to undergo surgery. During the preoperative treatment, the patient experienced anxiety and repeatedly bit and sucked the lip and cheek area. Clinically, white plaques and ulcers were seen with a wide elevation in the lip and cheek area. Management: Against patients conducted 0.9%NaCl compress 3 times a day and were given positive suggestions to reduce anxiety. Conclu-sion: In addition to topical medication for treatment of self-inflicted traumatic oral lesion, it is also necessary to give adequate care from health personnel and positive suggestion to reduce preoperative anxiety in pediatric patient who will undergo surgery.